نحو إنشاء معجم طوبونيمي لمدينة مغنية و ما جاورها – دراسة لغوية ثقافية: Towards Building up a Toponimic Dictionary about the Town of Maghnia And Its Nearabouts – A Linguistic And Cultural Study - بن عامر سعيد; وسيلة صالح (Maalim, 2021)
This research aims at shedding light on the toponyms found in the town of Maghnia and its nearabouts so as to study most of its cultural aspects and explicit them linguistically. We would discover those different epistemological dimensions that surround each of its places in order to expose its value in term of culture, geography, civilisation, politics and others.